Disparate Outcomes : A Multisectoral Nutrition Assessment and Gap Analysis of Vietnam’s Ethnic Minority Populations - World Bank Group (World Bank, Washington, DC, 2019)
On average, Vietnam has achieved remarkable improvements in nutritional status in recent decades, but improvements in national aggregates mask wide disparities and a persistent ‘very high’ burden among disadvantaged ethnic minority groups. Between 2000 and 2010, national stunting rates dropped from 36.5 percent to 24.2 percent. The decrease from 2010 to 2015 was not as great, but when the 2015 data are disaggregated according to ethnic group, the Kinh majority has a prevalence of 17.7 percent, whereas the prevalence in other ethnic groups is 32.0 percent. This pattern repeats itself for the prevalence of underweight (a significant drop nationally from 33.8 percent in 2000 to 14.1 percent in 2015 but a 9.7 percent prevalence in the Kinh ethnic group in 2015 versus 21.9 percent in other ethnic groups) and wasting (a decrease from 8.6 percent to 5.6 percent in national prevalence from 2000 to 2015 but a 9.1 percent prevalence for Kinh versus 5.5 percent for other ethnic groups (WB Assessment 2012). The gap between the ethnic majority and minority has persisted despite the multiple government programs aimed at reducing it. As the economy has evolved from predominantly agriculture to a mix of agriculture and technology, the requirements of the workforce have changed as well. Manual labor is still necessary but no longer enough. The need is for intelligent, highly educated and skilled workers. All of these attributes are the product of a healthy, well-nourished population. Deficiencies in nutrition and health, lower levels of education, lack of language skills in the national language, and inability to migrate to jobs in urban centers of ethnic minorities have further hindered their ability to narrow the gap in nutrition and economic well-being.